Strategi Guru Pendidikan Agama Islam Dalam Membentuk Karakter Kejujuran Peserta Didik - Muhammad Hendri; Ahmad Rivauzi (Prodi Pendidikan Keagamaan Islam, 2022)
Education is a process where students can actively develop their potential. In the educational process, Islamic Religious Education teachers have a great task of educating and instilling honest personalities in students. Effective ways to instill an honest attitude start from the family, school and community. In fact, there are still many students who do not speak or act honestly in the school environment. This is something the teacher should pay attention to. One solution to solve this problem is to use exemplary strategies, advice, and habituation. This study used a qualitative approach, data were collected through in-depth interviews with several informants in the category of educators and students in vocational high schools. The purpose of this study was to determine the strategy of PAI teachers in shaping the character of honesty as well as the supporting and inhibiting factors in the formation of the character of honesty. In this study, it was found that the principal and his staff used exemplary methods, advice, and habituation to shape the character of students at school. The results of the study show that teachers can provide good examples so that students can practice them in everyday life, and give advice wherever, whenever and this is done continuously, and with practice, students become accustomed to good manners and honest personalities. Supporting factors in the formation of the character of honesty with the presence of professional teachers and a more conducive school environment, as well as inhibiting factors in the formation of the character of honesty are the family environment and freedom in the use of gadgets. honesty character.